2007
DOI: 10.1007/s11695-007-9149-4
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Laparoscopic Adjustable Gastric Banding in Super-obese Patients

Abstract: Outpatient LAGB can be safely performed in super-obese patients with a complication rate similar to lower BMI patients. Patient selection and preoperative preparation are essential to achieve excellent outcomes. The decision to offer an outpatient LAGB should rest on the overall physiological condition rather than BMI or weight alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 9 publications
(6 reference statements)
2
35
0
2
Order By: Relevance
“…The procedure is quick, lasting an average of 35-95 min [10][11][12][13], which is important for obese patients with many coincidental pathologies, and it is associated with a low rate of serious complications as well as rare intra-and early postoperative complications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure is quick, lasting an average of 35-95 min [10][11][12][13], which is important for obese patients with many coincidental pathologies, and it is associated with a low rate of serious complications as well as rare intra-and early postoperative complications.…”
Section: Resultsmentioning
confidence: 99%
“…▬ Pleural injury with pneumothorax, which can be caused by too deep introduction (beyond the left diaphragmatic crux) of the tool used for retrogastric passage of the band ▬ Perforation of other parts of the gastrointestinal tract (most often the transverse colon) during insertion of the instruments without visual control or during coagulation. Such complications are rare [10,15]. ▬ Passing the band between the anterior gastric wall and the adipose tissue anterior to the stomach, possible in cases of abundant adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Skilled surgeons require roughly 1 h of operative time for completion of LAGB (8,18). Reported conversion rates to an open procedure have ranged from 0% in private practice settings to 8% at academic institutions where residents are involved (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic-adjustable gastric banding (LAGB) is a minimally invasive bariatric surgery with a low incidence of perioperative complications (2,3). Several trials have demonstrated that careful patient selection allows LAGB to be an ambulatory procedure (4)(5)(6)(7)(8)(9)(10). However, many of these prospective studies had small sample sizes with patients already preselected in observational trials.…”
mentioning
confidence: 99%
“…Torchia has managed to show 82 % EWL at 4 years follow up with 5 patients and 69.7 % in 55 patients at 2 years follow up [ 12 ]. Proponents of banding in extreme obesity draw attention to the near absence of mortality and morbidity when compared to LRYGB or LVSG; they also claim LAGB needs shorter operating times and length of hospital stay [ 13 ].…”
Section: Laparoscopic Adjustable Gastric Band (Lagb)mentioning
confidence: 99%